BUILDING INTEGRATION AND INTERCONNECTION IN ISLAMIC ECONOMIC SYSTEM TO CREATE ISLAMIC SOLUTIONS IN SOLVING SOCIAL PROBLEMS - Muhammad Rahman Bayumi; Rizal Alfit Jaya (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2018)
Social problems such as poverty, inequality, income distribution, lack of prosperity, social conflict, and others are problems that often appear in developing countries including Indonesia. As a pluralistic state, settlement of these problems cannot be resolved through a single approach, but through the use of various approaches of science, culture, and religion. There has been a lot of effort and solutions made by the government, organizations, and institutions concerned with solving problems that appear in Indonesia. However, there has been no significant impact on social problems. An appropriate approach that is perfect for creating Islamic solutions is to build integration and interconnection as an approach towards the Islamic economic system. In the approach of integration and interconnection, there are three principal characteristics. They are the semipermeable, intersubjective testability, and creative imagination. The third characteristic is some attempt to create an Islamic solution, applicable and revolutionary.===============================================Membangun Integrasi dan Interkoneksi Dalam Sistem Ekonomi Islam untuk Menciptakan Solusi Islam dalam Memecahkan Masalah Sosial - Masalah sosial seperti kemiskinan, ketidaksetaraan, distribusi pendapatan, kurangnya kemakmuran, konflik sosial, dan lain-lain adalah masalah yang sering muncul di negara berkembang termasuk Indonesia. Sebagai negara majemuk, penyelesaian masalah-masalah ini tidak dapat diselesaikan melalui pendekatan tunggal, tetapi melalui penggunaan berbagai pendekatan ilmu pengetahuan, budaya dan agama. Telah ada banyak upaya dan solusi yang dibuat oleh pemerintah, organisasi dan institusi yang peduli dengan penyelesaian masalah yang muncul di Indonesia. Namun, belum ada dampak yang signifikan terhadap masalah sosial. Pendekatan yang tepat yang sempurna untuk menciptakan solusi Islam adalah membangun integrasi dan interkoneksi sebagai pendekatan terhadap sistem ekonomi Islam. Dalam pendekatan integrasi dan interkoneksi, ada tiga karakteristik utama. Mereka adalah tesis yang mudah dipahami, intersubyektif, dan imajinasi kreatif. Karakteristik ketiga adalah beberapa upaya untuk menciptakan solusi Islami, aplikatif dan revolusioner.